Sleepiness and daily sleep of Malaysian shift workers in electronics manufacturing industry - Mohd Shahril, Abu Hanifah; Mohamad Ezuan, Abdul Jalil; Norazura, Ismail (Malaysian Public Health Physicians’ Association, 2020)
The purpose of this study was to identify the relationship between sleepiness and daily sleep amount, and its significant associated factors among shift workers of the electronics manufacturing industry in Malaysia. 300 shift workers were asked to respond to a survey on demographic information, sleepiness and daily sleep. Sleepiness was surveyed by using the Karolinska Sleepiness Scale and daily sleep was captured by using sleep diary. A total of 255 employees provided valid data for analysis. To test the hypothesis, statistical analysis was conducted using IBM SPSS program version 24. Sleepiness among shift workers found to be increased by the end of the shift. Around 30% of workers did not have an adequate amount of daily sleep. Sleepiness was found to have significant associations with age, marital status, level of education, time of shift, and working experience. Meanwhile, the amount of daily sleep obtained was only significantly associated with the age of the respondents. There is no significant relationship found between sleepiness and daily sleep of the shift workers. Shift workers in the electronics manufacturing industry in Malaysia were exposed to sleepiness at work and reduction in their daily sleep. This will increase the risk of an accident in the workplace. Appropriate intervention program should be implemented to curb this problem.